Proposed new interior design for Taska Pusat Anak Permata (Seri Iskandar Branch ) at Taska Pusat Anak Permata Cawangan Perak Tengah 32600 Bandar Seri Iskandar Perak Darul Ridzuan / Nurul Izzah Farizzah Idrus - Idrus, Nurul Izzah Farizzah (Faculty of Architecture, Planning and Surveying, 2011)
A final year student pursuing a diploma course in Interior Design is required to prepare a final year project. The design of the project should be related closely to current issues or similar to it. The knowledge and skill acquired during the duration of the course should be put to practise and onto the drawing board. This also includes the research, case study, interviewing of clients, designing proposals, preparing art work, preparing presentation drawings, design development and last but not least the final presentation. In this project report, to produce a successful design, the process of designing should be based upon detailed research and observation and every aspect should be identified. The project proposal chosen for this semester final project is proposed upgrading and new interior design for Taska Pusat Anak Permata (Seri Iskandar Branch), at Taska Pusat Anak Permata Cawangan Seri Iskandar,32600 Bandar Seri Iskandar.Perak.The main objectives of this project proposal are to introduce new spaces that suitable for the kids daily activities in the Taska Pusat Anak Permata and proposed new image design for it which has the look of an international child care and learning centre and modern image as to bring the image Taska Pusat Anak Permata name internationally. With the design proposal of Taska Pusat Anak Permata, hope to gives out suitable environment for the place. Concept and image are also bring a huge implementation for the design proposal, so that I would like to proposed new concept and image for this Taska Pusat Anak Permata. In this project proposal I will try my best to produce a good design proposal for Pusat Anak Permata as to make the taska known internationally.